Genetic analysis of morphometric traits of Sirohi goats - SHARMA, M C; PATHODIYA, O P; SHARMA, S K; GURJAR, M L; TAILOR, S P (The Indian Journal of Animal Sciences, 2011)
Morphometric traits, viz. body height, body length and body girth at birth, 3, 6, 9 and 12 l1J.onths of age in Sirohi kids were analyzed according to genetic and non-genetic factor like sire, location year of birth. season of birth. sex of kid and type of birth. Results revealed that the positive and high genetic and phenotypic corelations between 3 and 6 months morphometric traits and with other traits indicated that selection of kids may be done on the basis of 3 or 6 Illonths morphon1etric traits in order to obtain higher value of morphmetlic traits at later ages. Managetnent condition should be improved to gain profit from goat rearing.Â